Demystifying Urban Curbside Freight Management: Strategic Incremental Approach from Washington, D.C. Issue 12 (December 2019) - Dey, Soumya S.; Pérez, Benito O.; Richards, Laura; Pochowski, Alek; Sanders, Meredyth; Darst, Matt; Sanchez, Eduardo Cardenas; Dock, Stephanie
Loading zones and commercial vehicle activity are issues in cities across the country including the District of Columbia. Like other major U.S. cities, the District Department of Transportation (DDOT) has tried a variety of initiatives to alleviate the strain commercial vehicle activity places on the overall transportation system. These include metering or otherwise pricing loading zones and parking, expanding the size and increasing the number of loading zones, increasing the number of metered parking spaces, extending loading and metering time periods, simplifying and standardizing truck parking rules, and encouraging nighttime or off-peak goods delivery. These initiatives have had some success but a more targeted approach was needed, especially to address non-commercial vehicles parking in loading zones and thus pushing delivery vehicles to double park while loading and unloading. As part of the parkDC: Penn Quarter/Chinatown performance parking pilot, DDOT attempted to reduce the number of illegally parked cars blocking loading zones by raising prices to the highest prevailing rate on the blockface and increasing loading zone availability by extending the hours of operation of loading zones. Moving forward, DDOT has identified several next steps including: oversize/overweight vehicle routing, increased and targeted loading zone enforcement, increased disincentives for violations, data-driven modifications to the loading zone program, and modifications to the pay-by-cell program to mitigate non-trucks paying to park in loading zones. As gaps in understanding curbside movement close with increased data availability, the District expects the programs associated with curbside management to evolve to reflect smarter policy, program, and management practices.